Nature exposure might be the intervention to improve the self-regulation and skilled performance in mentally fatigue athletes: A narrative review and conceptual framework - Sun, He; Soh, Kim G.; Roslan, Samsilah; Wazir, Mohd Rozilee Wazir Norjali; Mohammadi, Alireza; Ding, Cong; Zhao, Zijian (Frontiers in Psychology, 2022)
Background: Due to causing inability of self-regulation (ego depletion) and executive functions such as directed attention and visual searching for relevant information (e.g., the ball location and the position of teammates), mental fatigue impairs skilled performance in various sports. On the other hand, natural scenes could improve directed attention, which considerably benefits visual searching ability and self-regulation However, nature exposure as a potential intervention to improve skilled performance among mentally fatigued athletes has never been discussed. Purpose: The current review was to propose the potential intervention for the impairment of skilled performance among mentally fatigued athletes, and generate a framework for future studies based on retrieving literature from several databases (PubMed, Web of Science, Scopus, and EBSCOhost). Results: Thirty-three works of literature including thirty-eight experiments (mental fatigue 14; ego depletion 5; and nature exposure 18) were obtained. Finally, a conceptual framework was built regarding the effect of nature exposure intervention on skilled performance in athletes for future studies. Conclusion: Nature exposure may be an effective intervention to improve skilled performance in athletes after the prior mental exertion (e.g., mental fatigue). The directed attention may be the third factor in the Psychobiological Model of Exercise Performance to prevent reduced performance declines as mental fatigue is minimized and improve skilled performance.